Detection of toxoplasmic encephalitis in HIV positive patients in urine with hydrogel nanoparticles. - Hannah E Steinberg; Natalie M Bowman; Andrea Diestra; Cusi Ferradas; Paul Russo; Daniel E Clark; Deanna Zhu; Ruben Magni; Edith Malaga; Monica Diaz; Viviana Pinedo-Cancino; Cesar Ramal Asayag; et al. (PLoS Neglected Tropical Diseases, 2021)
Background Diagnosis of toxoplasmic encephalitis (TE) is challenging under the best clinical circumstances. The poor clinical sensitivity of quantitative polymerase chain reaction (qPCR) for Toxoplasma in blood and CSF and the limited availability of molecular diagnostics and imaging technology leaves clinicians in resource-limited settings with few options other than empiric treatment. Methology/principle findings Here we describe proof of concept for a novel urine diagnostics for TE using Poly-N-Isopropylacrylamide nanoparticles dyed with Reactive Blue-221 to concentrate antigens, substantially increasing the limit of detection. After nanoparticle-concentration, a standard western blotting technique with a monoclonal antibody was used for antigen detection. Limit of detection was 7.8pg/ml and 31.3pg/ml of T. gondii antigens GRA1 and SAG1, respectively. To characterize this diagnostic approach, 164 hospitalized HIV-infected patients with neurological symptoms compatible with TE were tested for 1) T. gondii serology (121/147, positive samples/total samples tested), 2) qPCR in cerebrospinal fluid (11/41), 3) qPCR in blood (10/112), and 4) urinary GRA1 (30/164) and SAG1 (12/164). GRA1 appears to be superior to SAG1 for detection of TE antigens in urine. Fifty-one HIV-infected, T. gondii seropositive but asymptomatic persons all tested negative by nanoparticle western blot and blood qPCR, suggesting the test has good specificity for TE for both GRA1 and SAG1. In a subgroup of 44 patients, urine samples were assayed with mass spectrometry parallel-reaction-monitoring (PRM) for the presence of T. gondii antigens. PRM identified antigens in 8 samples, 6 of which were concordant with the urine diagnostic. Conclusion/significances Our results demonstrate nanoparticle technology's potential for a noninvasive diagnostic test for TE. Moving forward, GRA1 is a promising target for antigen based diagnostics for TE.